Comparison of volumetric responses to different corticosteroid administration methods in IgG4-related ophthalmic disease - Min Kyu Yang; Seong Jung Ha; Ho-Seok Sa (PLoS ONE, 2025)
Purpose To analyze the clinical and volumetric responses to different corticosteroid administration methods for IgG4-related ophthalmic disease (IgG4-ROD). Methods The medical records of patients with bilateral lacrimal gland (LG) enlargement diagnosed with IgG4-ROD through unilateral LG biopsy between January 2011 and January 2022 were retrospectively reviewed. Clinical signs and the non-biopsied LG volume across three administration routes were compared: oral prednisolone (Pd), intravenous (IV) methylprednisolone (methylPd), and local triamcinolone (TA) injection. Radiological relapse was defined as the first instance of failure to satisfy the radiological response criteria, i.e., a post-treatment volume of <1.0 cm 3 or a post-treatment to pre-treatment volume ratio of <35%. Results Among the 28 patients, eight, ten, and ten received oral Pd, IV methylPd, and local TA injection, respectively. No significant differences were observed between the groups in terms of the baseline characteristics. Ophthalmic adverse effects were not observed in any patient. Kaplan–Meier survival analysis revealed that the 2-year radiological relapse-free survival in the IV methylPd group (80.0%) was higher than that in the oral Pd group (37.5%, p = 0.036) but comparable with that in the local TA group (100.0%, p = 0.886). The median post-treatment to pre-treatment volume ratio in the IV methylPd group (35.4%) was significantly lower than that in the oral Pd group (75.0%, p = 0.042) but comparable with that in the local TA injection group (38.5%, p = 0.321) one year after treatment. Conclusion Compared with oral Pd, IV methylPd yielded better and more sustained radiological responses in patients with LG-involving IgG4-ROD. Local TA injection was also an effective alternative treatment option.